Lithuania in Russian Epos (On the Poetics of Names) - N. Mitropolskaja (Literatūra (Vilnius))
The image of the poetical name Lithuania (Lietuvos) extends far beyond historical and geographical boarders. It is an epic image of a neighbouring or even a far remote country. The image acquires aesthetic function and becomes a part of poetical formulae.